Analisa Prediksi Penjualan Produk Dengan Menggunakan Metode C4.5 (Studi Kasus: PT. Kawan Lama Ace Hardware) - Muhammad Rizal Lubis (JURIKOM (Jurnal Riset Komputer), 2019)
PT. Kawan Lama Ace Hardware is a retail company engaged in lifestyle equipment and products. More than 3,500 types of products are available at competitive prices, fulfilling almost all the daily needs of consumers. PT. Kawan Lama Ace Hardware lacks analysis of sales of goods and entry of goods or inventory in the warehouse, besides that the company has never analyzed the sales of goods so it does not know whether the previous year's product sales are more than the current year and what products are most in demand in the company while the number Such large data can be a problem and overwhelmed in calculating existing products at the company requires a Tanagra application that can classify the results of sales of car products.